Ustrojowe uwarunkowania funkcjonowania partii politycznych we Francji i ich konsekwencje dla sceny politycznej - Anna Pacześniak (Ksiegarnia Akademicka Publishing, 2020)
Systemic Conditions of Functioning of Political Parties in France and Their Consequences for the Political Scenario